Increased proinflammatory cytokine production in adipose tissue of obese patients with chronic kidney disease - Teplan, Vladimír; Vyhnánek, Frantisek; Gürlich, Robert; Haluzík, Martin; Racek, Jaroslav; Vyhnankova, Ivana; Stollová, Milena; Teplan, Vladimír (Wiener klinische Wochenschrift, 2010)
BACKGROUND: Obesity is a known high-risk factor for the development of vascular diseases and chronic kidney disease (CKD). In this study we aimed to elucidate the impact of adipose tissue on the inflammatory state in CDK patients with obesity. PATIENTS AND METHODS: A cohort of 40 patients with CKD (stages 3-4) with mild proteinuria (2.3-3.5 g/day) were analyzed in a prospective cross-sectional study: single blood samples and visceral and subcutaneous samples of adipose tissue were taken from 20 patients with obesity and 20 without obesity (control group) during elective abdominal surgery (laparoscopic cholecystectomy). Serum concentrations of asymmetric dimethylarginine (ADMA), adiponectin, C-reactive protein, interleukin-6, tumor necrosis factor-alpha, pentosidine and monocyte chemoattractant protein-1 were measured. Messenger RNA expression of tumor necrosis factor-alpha, monocyte chemoattractant protein-1, adiponectin receptors 1 and 2, and immunocompetent cell marker CD68 was measured in subcutaneous and visceral fat samples using real-time PCR. Adipose tissue was examined immunohistochemically for CD68-positive cells. Other biochemical parameters (insulin, glycated hemoglobin, cholesterol, LDL cholesterol, and triglycerides) were assessed in the two groups of patients at the same time. RESULTS: Serum concentrations of ADMA, C-reactive protein, pentosidine, interleukin-6, tumor necrosis factor-alpha and monocyte chemoattractant protein-1 were significantly higher in obese CKD patients than in the control group; adiponectin was lower in the obese group. Subcutaneous and visceral mRNA expressions of tumor necrosis factor-alpha, CD68, adiponectin receptor-1, and monocyte chemoattractant protein-1 were significantly increased in the obese patients, whereas expression of adiponectin, interleukin-6, and adiponectin receptor-2 did not significantly differ between the patient groups. In general, mRNA expressions were higher in visceral than in subcutaneous samples (P < 0.01 vs. P < 0.05). Increased infiltration of subcutaneous and visceral adipose tissue by CD68-positive immunocompetent cells was found in the obese CKD group. With respect to lipid metabolism parameters, a small but significant increase in levels was found in the obese patients (P < 0.02). Changes in triglycerides were more marked in this group (P < 0.01) and a similar increase was noted in insulin and HbA1c levels (P < 0.02). CONCLUSION: Increased expression of proinflammatory cytokines and increased infiltration by immunocompetent cells were found in adipose tissue of obese patients with CKD stages 3-4. This upregulated inflammation may contribute to the induction of a systemic proinflammatory state in patients with CKD and could accelerate the progression of renal dysfunction.
Keywords: zánět; Female; Cytokines; Tissue Distribution; ženské pohlaví; Renal Insufficiency, Chronic; Obesity; cytokiny; imunologické faktory; lidé; chronická renální insuficience; Inflammation; Immunologic Factors; obezita; Male; tkáňová distribuce; lidé středního věku; tuková tkáň; mužské pohlaví; Adipose Tissue; Middle Aged; Humans